Tumor progression locus 2 (TPL2) in tumor-promoting Inflammation, Tumorigenesis and Tumor Immunity - Njunge, Lucy Wanjiru (Theranostics, 2020)
Over the years, tumor progression locus 2 (TPL2) has been identified as an essential modulator of immune responses that conveys inflammatory signals to downstream effectors, subsequently modulating the generation and function of inflammatory cells. TPL2 is also differentially expressed and activated in several cancers, where it is associated with increased inflammation, malignant transformation, angiogenesis, metastasis, poor prognosis and therapy resistance. However, the relationship between TPL2-driven inflammation, tumorigenesis and tumor immunity has not been addressed. Here, we reconcile the function of TPL2-driven inflammation to oncogenic functions such as inflammation, proliferation, apoptosis resistance, angiogenesis, metastasis, immunosuppression and immune evasion. We also address the controversies reported on TPL2 function in tumor-promoting inflammation and tumorigenesis, and highlight the potential role of the TPL2 adaptor function in regulating the mechanisms leading to pro-tumorigenic inflammation and tumor progression. We discuss the therapeutic implications and limitations of targeting TPL2 for cancer treatment. The ideas presented here provide some new insight into cancer pathophysiology that might contribute to the development of more integrative and specific anti-inflammatory and anti-cancer therapeutics.